The Future of Management Education Volume 2: Differentiation Strategies for Business Schools (Palgrave Macmillan UK, 2018)
This book discusses the challenges facing business schools and management education systems around the world. Based on documented descriptions of institutional and competitive dynamics in the 'industry' of management education, the authors show how management education is going through major changes such as new governance and business models, mergers and acquisitions, internationalisation of faculty and students coexisting with entrenchment in local markets, ever more needs for financial resources, development of distant and blended learning, and increasing pressure for research output to boost rankings. With concerns surrounding the sustainability of current trends in faculty salary inflation, social acceptability of higher fees, cost of distance learning and the risk of an academic-industry divide around knowledge produced by management research, The Future of Management Education develops an analysis of business models and discusses strategic implications for stakeholders. The second volume extends the discussion to a total of 23 countries to bring a genuinely global perspective and move away from the Euro-centric outlook. The countries covered in the second volume include China, Brazil, Russia, Singapore and France.